(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Bats and human biological structures are believed to be similar in terms of phylogeny, reproductive biology, and early development. Adequate knowledge of placental morphology will have important implications for research and in comparative anatomy. This report is a part of on-going studies on the African fruit bat species and is a case report from an incidental discovery of the foetus and placenta in an African fruit bat (Epomops franqueti) captured for research.